2014
DOI: 10.1080/02615479.2014.926320
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be a Social Worker in a Non-traditional Placement: Critical Reflections on Social Work, Professional Identity and Social Work Education in England

Abstract: Background: Cognitive Muscular TherapyTM (CMT) is an integrated behavioural intervention developed for knee osteoarthritis. CMT teaches patients to reconceptualise the condition, integrates muscle biofeedback and aims to reduce muscle overactivity, both in response to pain and during daily activities. This nested qualitative study explored patient and physiotherapist perspectives and experiences of CMT.Methods: Five physiotherapists were trained to follow a well-defined protocol and then delivered CMT to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…(Student A) Despite the speaker's apparent uncertainty, the reference to occupational standardsused to assess students' progress while on their practice placements -formed a common pattern across all the transcripts. Similar findings are reported by Scholar et al, (2014) whose three year study of a much larger sample of social work degree students found that, especially in the earlier stages of training, participants explained social work in relation to traits. Generic professional traits are summarised by Yam (2004, p.929) as an 'extensive theoretical knowledge base'; 'expertise in a specialized field'; an 'altruistic commitment to service'; an 'unusual degree of autonomy in work'; 'a code of ethics and conduct overseen by a body of representatives from within the field itself'; and 'a personal identity that stems from the professional's 8 occupation'.…”
Section: Professional Traitssupporting
confidence: 86%
“…(Student A) Despite the speaker's apparent uncertainty, the reference to occupational standardsused to assess students' progress while on their practice placements -formed a common pattern across all the transcripts. Similar findings are reported by Scholar et al, (2014) whose three year study of a much larger sample of social work degree students found that, especially in the earlier stages of training, participants explained social work in relation to traits. Generic professional traits are summarised by Yam (2004, p.929) as an 'extensive theoretical knowledge base'; 'expertise in a specialized field'; an 'altruistic commitment to service'; an 'unusual degree of autonomy in work'; 'a code of ethics and conduct overseen by a body of representatives from within the field itself'; and 'a personal identity that stems from the professional's 8 occupation'.…”
Section: Professional Traitssupporting
confidence: 86%
“…There is some anecdotal evidence to suggest that over this period, in parts of the country at least, Newly Qualified Social Workers (NQSWs) without statutory experience on placement have struggled to find employment in statutory children's social work (Community Care Discussion 13.1.2014), and that opportunities in statutory settings within adult social work have been reducing (CFI 2012:2). Previous research on 'non-traditional' social work placements, and placements inside and outside the statutory sector has suggested that some social work students are making decisions not to pursue careers in the statutory sector at all (Scholar, McLaughlin, McCaughan et al 2014), but see roles in the independent and voluntary sectors as offering more opportunities to carry out 'real social work'. Paradoxically though, in such posts it appears that they may not feel that they can describe themselves as 'social workers'.…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting finding that is likely to have repercussions for social work education more widely than education pertaining to a career with older people because it suggests that social work education may need to i. pay more attention to the principles of the profession by enhancing students abilities to develop practice, organisational and managerial knowledge and skills that engender inclusion, transparency and equality within the context of dispersed and varied practice settings (Scholar et al, 2014), ii.…”
Section: Social Work Educationmentioning
confidence: 99%
“…Interdisciplinary opportunities will also build the capacity and capability of social workers to be confident and supported in their role. These opportunities will also enhance the ability of social workers to translate professional principles and theory into practice and strengthen their resilience to hold firm to their professional ethics and values in the face of competing agendas (Green & Sawyer, 2010;Scholar, McLaughlin, McCaughan, & Coleman 2014). This process of forming a stronger connection to the profession and a commitment to working collaboratively with others does not rest solely with practice.…”
Section: Practice With Older Peoplementioning
confidence: 99%
See 1 more Smart Citation